Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Durability of the moderate-to-heavy intensity transition can be predicted using readily available markers of physiological decoupling - Jeffrey A. Rothschild; Gabriele Gallo; Kate Hamilton; Julian D. Stevenson; Harrison Dudley-Rode; Thanchanok Charoensap; Daniel J. Plews; Andrew E. Kilding; Ed Maunder (European Journal of Applied Physiology, 2025)
Purpose To assess relationships between heart rate (HR), ventilation (̇ $$\dot V$$ V ˙ E ), and respiratory frequency (F R ) decoupling and durability of the first ventilatory threshold (VT 1 ), and the strength of practical models to predict power output at VT 1 during prolonged exercise. Methods Durability of VT 1 was assessed via measurements of power output at VT 1 before and after ~ 2.5-h of initially moderate-intensity cycling in 51 trained cyclists, as part of four studies published elsewhere. In 12 of those participants, power output at VT 1 was assessed every hour until task failure. For every assessment of power output at VT 1 , HR, F R , and $$\dot V$$ V ˙ ̇ E was measured at fixed power outputs, and thus decoupling of these variables with power output was determined. Bivariate repeated-measures correlations (r rm ) between decoupling and durability of VT 1 were assessed. Multivariable models were created to predict power output at VT 1 during prolonged exercise using generalised estimating equations. Results Negative correlations were observed between exercise-induced change in power output at VT 1 and HR (r rm = −0.76, P < 0.001) and F R (r rm = −0.40, P = 0.013) decoupling, but not $$\dot V$$ V ˙ ̇ E decoupling (r rm = −0.25, P = 0.136). The final prediction model, containing baseline VT 1 and peak oxygen uptake, F R decoupling, and an interaction between HR decoupling and exercise duration, effectively predicted real-time VT 1 (mean absolute error, ~ 7.2 W; R 2 , 0.95). Conclusion HR and/or F R decoupling during controlled training sessions may be a practically useful durability assessment. Our prediction models may be an effective means of improving within-session intensity regulation and training load monitoring.

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Mitochondrial uncoupling and glycolysis stimulation are beneficial for kinematics, functionality and oxidative homeostasis of cryopreserved ram sperm - Álvaro de Miranda Alves; João Diego de Agostini Losano; Roberta Ferreira Leite; Bruno Rogério Rui; Daniel de Souza Ramos Angrimani; Thais Rose dos Santos Hamilton; Camilla Mota Mendes; Mayra Elena Ortiz D'Avila Assumpção; Marcilio Nichi (Cryobiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Frequent disturbance to a foundation species disrupts consumer‐mediated nutrient cycling in giant kelp forests - Joseph R. Peters; Daniel C. Reed; June Shrestha; Scott L. Hamilton; Deron E. Burkepile (Ecology, 2025)
Structure‐forming foundation species facilitate consumers by providing habitat and refugia. In return, consumers can benefit foundation species by reducing top‐down pressures and increasing the supply of nutrients. Consumer‐mediated nutrient dynamics (CND) fuel the growth of autotrophic foundation species and generate more habitat for consumers, forming reciprocal feedbacks. Such feedbacks are threatened when foundation species are lost to disturbances, yet testing these interactions requires long‐term studies, which are rare. Here, we experimentally evaluated how disturbance to giant kelp, a marine foundation species, affects (1) CND of the forest animal community and (2) nutrient feedbacks that help sustain forest primary production during extended periods of low nitrate. Our experiment involved removing giant kelp annually during the winter for 10 years at four sites to mimic frequent wave disturbance. We paired temporal changes in the forest community in kelp removal and control plots with estimates of taxon‐specific ammonium excretion rates (reef fishes and macroinvertebrates) and nitrogen (N) demand (giant kelp and understory macroalgae) to determine the effects of disturbance on CND as measured by ammonium excretion, N demand by kelp forest macroalgae, and the percentage of nitrogen demand met by ammonium excretion. We found that disturbance to giant kelp decreased ammonium excretion by 66% over the study, mostly due to declines in fishes. Apart from a few fish species that dominated CND, most reef‐associated consumers were unaffected by disturbance. Disturbance to giant kelp reduced its N demand by 56% but increased that of the understory by 147% due to its increased abundance in the absence of a kelp canopy. Overall, disturbance had little effect on the fraction of N demand of macroalgae met by consumer excretion due to the offsetting responses of giant kelp, understory macroalgae, and consumers to disturbance. Across both disturbance regimes, on average, consumers supported 11%–12% of the N required by all kelp forest macroalgae and 48% of N demand by the understory macroalgae (which are confined to the benthos where most reef‐associated consumers reside). Our findings suggest that CND constitutes a considerable contribution of N required in kelp forests, yet nutrient inputs decrease following reductions in essential habitat perpetuated by frequent disturbances.

Influence of water source on alpine stream community structure: linking morphological and metabarcoding approaches - Daniel L. Preston; Scott Hotaling; Isabella M. Errigo; Paul B. Frandsen; Taylor L. Price; Trinity L. Hamilton; Kurt E. Anderson; Samuel E. Yevak; Jennifer F. Morse (Aquatic Sciences, 2025)

Establishing an optimized flotation scheme for a complex Base-Metal sulfide ore using a modified xanthate reagent scheme - Daniel Hamilton; Wonjae Chang; Kerry N. McPhedran (Minerals Engineering, 2024)

Durability of the moderate-to-heavy-intensity transition is related to the effects of prolonged exercise on severe-intensity performance - Kate Hamilton; Andrew E. Kilding; Daniel J. Plews; Mathew J. Mildenhall; Mark Waldron; Thanchanok Charoensap; Tobias H. Cox; Matthew J. Brick; Warren B. Leigh; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose Power output at the moderate-to-heavy-intensity transition decreases during prolonged exercise, and resilience to this has been termed ‘durability’. The purpose of this study was to assess the relationship between durability and the effect of prolonged exercise on severe-intensity performance, and explore intramuscular correlates of durability. Methods On separate days, 13 well-trained cyclists and triathletes (V̇O 2 peak, 57.3 ± 4.8 mL kg −1 min −1 ; training volume, 12 ± 2.1 h week −1 ) undertook an incremental test and 5-min time trial (TT) to determine power output at the first ventilatory threshold (VT 1 ) and severe-intensity performance, with and without 150-min of prior moderate-intensity cycling. A single resting vastus lateralis microbiopsy was obtained. Results Prolonged exercise reduced power output at VT 1 (211 ± 40 vs. 198 ± 39 W, ∆ -13 ± 16 W, ∆ -6 ± 7%, P = 0.013) and 5-min TT performance (333 ± 75 vs. 302 ± 63 W, ∆ -31 ± 41 W, ∆ -9 ± 10%, P = 0.017). The reduction in 5-min TT performance was significantly associated with durability of VT 1 (r s = 0.719, P = 0.007). Durability of VT 1 was not related to vastus lateralis carnosine content, citrate synthase activity, or complex I activity ( P > 0.05). Conclusion These data provide the first direct support that durability of the moderate-to-heavy-intensity transition is an important performance parameter, as more durable athletes exhibited smaller reductions in 5-min TT performance following prolonged exercise. We did not find relationships between durability and vastus lateralis carnosine content, citrate synthase activity, or complex I activity.

Migration of transition metals and potential for carbon mineralization during acid leaching of processed kimberlite from Venetia diamond mine, South Africa - Baolin Wang; Nina Zeyen; Sasha Wilson; Makoto J. Honda-McNeil; Jessica L. Hamilton; Konstantin Von Gunten; Daniel S. Alessi; Thomas R. Jones; David J. Paterson; Gordon Southam (Applied Geochemistry, 2024)

Assessment of rapid wastewater surveillance for determination of communicable disease spread in municipalities - Mohsen Asadi; Daniel Hamilton; Corwyn Shomachuk; Femi F. Oloye; Chantel De Lange; Xia Pu; Charles A. Osunla; Jenna Cantin; Seba El-Baroudy; Edgard M. Mejia; Branden Gregorchuk; Michael G. Becker; et al. (Science of The Total Environment, 2023)

Metagenomic analysis of ethylene glycol contamination in anaerobic digestion - Gabrielle R. Joslin; Daniel G. Barber; Lindsay Aston; Ping Liu; Olukayode Kuloyo; Kangsa Oentoro; Jiayi Liu; Ashley V. Baugh; Jeffrey R. Fedenko; Ioannis Melas; Phillip G. Hamilton; Damian J. Allen; et al. (Bioresource Technology, 2023)

Miocene tropical storms: Carbonate framework approaches and geochemistry proxies in a reservoir model - Orangel Aguilera; Olga M. Oliveira De Araújo; Ricardo Tadeu Lopes; Marcelo Cohen; Dayana Alvarado Sierra; Beatriz Teixeira Guimarães; Ana Paula Linhares; Félix Rodriguez; Manuel Moreira; Rut Díaz; Hamilton Santos Gama Filho; Marcelino Jose Dos Anjos; et al. (Marine and Petroleum Geology, 2023)

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Review of the Opportunities and Challenges for Using Remote Sensing for Management of Surface-Canopy Forming Kelps - Kyle C. Cavanaugh; Tom Bell; Maycira Costa; Norah E. Eddy; Lianna Gendall; Mary G. Gleason; Margot Hessing-Lewis; Rebecca Martone; Meredith McPherson; Ondine Pontier; Luba Reshitnyk; Rodrigo Beas-Luna; et al. (Frontiers in Marine Science, 2021)
Surface-canopy forming kelps provide the foundation for ecosystems that are ecologically, culturally, and economically important. However, these kelp forests are naturally dynamic systems that are also threatened by a range of global and local pressures. As a result, there is a need for tools that enable managers to reliably track changes in their distribution, abundance, and health in a timely manner. Remote sensing data availability has increased dramatically in recent years and this data represents a valuable tool for monitoring surface-canopy forming kelps. However, the choice of remote sensing data and analytic approach must be properly matched to management objectives and tailored to the physical and biological characteristics of the region of interest. This review identifies remote sensing datasets and analyses best suited to address different management needs and environmental settings using case studies from the west coast of North America. We highlight the importance of integrating different datasets and approaches to facilitate comparisons across regions and promote coordination of management strategies.

Respiration cycle duration and seawater flux through open blowholes of humpback ( Megaptera novaeangliae ) and North Atlantic right ( Eubalaena glacialis ) whales - Maria Clara Iruzun Martins; Carolyn Miller; Phillip Hamilton; Jooke Robbins; Daniel P. Zitterbart; Michael Moore (Marine Mammal Science, 2020)
Little is known about the dynamics of baleen whale respiratory cycles, especially the mechanics and activity of the blowholes and their interaction with seawater. In this study, the duration of complete respiration cycles (expiration/inhalation events) were quantified for the first time in two species: North Atlantic right whale (NARW) and humpback whale (HW) using high resolution, detailed imagery from an unoccupied aerial system (UAS). The mean duration of complete respiration cycles (expiration/inhalation event) in the NARW and HW were 3.07 s ( SD = 0.503, n = 15) and 2.85 s ( SD = 0.581, n = 21), respectively. Furthermore, we saw no significant differences in respiration cycle duration between age and sex classes in the NARW, but significant differences were observed between age classes in the HW. The observation of seawater covering an open blowhole was also quantified, with NARW having 20% of all breaths with seawater presence versus 90% in HW. Seawater incursion has not been described previously and challenges the general consensus that water does not enter the respiratory tract in baleen whales. Prevalent seawater has implications for the analysis and interpretation of exhaled respiratory vapor/mucosa samples, as well as for the potential inhalation of oil in spills.

Iodine status in western Kenya: a community-based cross-sectional survey of urinary and drinking water iodine concentrations - Michael J. Watts; Daniel R. S. Middleton; Andrew Marriott; Olivier S. Humphrey; Elliott Hamilton; Valerie McCormack; Diana Menya; Jessica Farebrother; Odipo Osano (Environmental Geochemistry and Health, 2020)

Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.

Peg-manipulation capabilities of middle-aged adults have a greater influence on pegboard times than those of young and old adults - Awad M. Almuklass; Daniel F. Feeney; Diba Mani; Landon D. Hamilton; Roger M. Enoka (Experimental Brain Research, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Peg-manipulation capabilities during a test of manual dexterity differ for persons with multiple sclerosis and healthy individuals - Awad M. Almuklass; Daniel F. Feeney; Diba Mani; Landon D. Hamilton; Roger M. Enoka (Experimental Brain Research, 2017)

Contrasting cyanobacterial communities and microcystin concentrations in summers with extreme weather events: insights into potential effects of climate change - Susanna A. Wood; Hugo Borges; Jonathan Puddick; Laura Biessy; Javier Atalah; Ian Hawes; Daniel R. Dietrich; David P. Hamilton (Hydrobiologia, 2017)

Investigating Cross‐Sectoral Synergies through Integrated Aquaculture, Fisheries, and Agriculture Phosphorus Assessments: A Case Study of Norway - Helen A. Hamilton; Eva Brod; Ola S. Hanserud; Erik O. Gracey; Magnus I. Vestrum; Anne Bøen; Franciska S. Steinhoff; Daniel B. Müller; Helge Brattebø (Journal of Industrial Ecology, 2016)
Summary Future phosphorus (P) scarcity and eutrophication risks demonstrate the need for systems‐wide P assessments. Despite the projected drastic increase in world‐wide fish production, P studies have yet to include the aquaculture and fisheries sectors, thus eliminating the possibility of assessing their relative importance and identifying opportunities for recycling. Using Norway as a case, this study presents the results of a current‐status integrated fisheries, aquaculture, and agriculture P flow analysis and identifies current sectoral linkages as well as potential cross‐sectoral synergies where P use can be optimized. A scenario was developed to shed light on how the projected 2050 fivefold Norwegian aquaculture growth will likely affect P demand and secondary P resources. The results indicate that, contrary to most other countries where agriculture dominates, in Norway, aquaculture and agriculture drive P consumption and losses at similar levels and secondary P recycling, both intra‐ and cross‐sectorally, is far from optimized. The scenario results suggest that the projected aquaculture growth will make the Norwegian aquaculture sector approximately 4 times as P intensive as compared to agriculture, in terms of both imported P and losses. This will create not only future environmental challenges, but also opportunities for cross‐sectoral P recycling that could help alleviate the mineral P demands of agriculture. Near‐term policy measures should focus on utilizing domestic fish scrap for animal husbandry and/or fish feed production. Long‐term efforts should focus on improving technology and environmental systems analysis methods to enable P recovery from aquaculture production and manure distribution in animal husbandry.

Creation of a high spatio‐temporal resolution global database of continuous mangrove forest cover for the 21st century (CGMFC‐21) - Stuart E. Hamilton; Daniel Casey (Global Ecology and Biogeography, 2016)
Aim To provide high‐resolution local, regional, national and global estimates of annual mangrove forest area from 2000 through to 2012 with the goal of driving mangrove research questions pertaining to biodiversity, carbon stocks, climate change, functionality, food security, livelihoods, fisheries support and conservation that have been impeded until now by a lack of suitable data. Location Global, covering 99% of all mangrove forests. Methods We synthesized the Global Forest Change database, the Terrestrial Ecosystems of the World database and the Mangrove Forests of the World database to extract mangrove forest cover at high spatial and temporal resolutions. We then used the new database to monitor mangrove cover at the global, national and protected area scales. Results Countries showing relatively high amounts of mangrove loss include Myanmar, Malaysia, Cambodia, Indonesia and Guatemala. Indonesia remains by far the largest mangrove‐holding nation, containing between 26% and 29% of the global mangrove inventory with a deforestation rate of between 0.26% and 0.66% per year. We have made our new database, CGMFC‐21, freely available. Main conclusions Global mangrove deforestation continues but at a much reduced rate of between 0.16% and 0.39% per year. Southeast Asia is a region of concern with mangrove deforestation rates between 3.58% and 8.08%, this in a region containing half of the entire global mangrove forest inventory. The global mangrove deforestation pattern from 2000 to 2012 is one of decreasing rates of deforestation, with many nations essentially stable, with the exception of the largest mangrove‐holding region of Southeast Asia. We provide a standardized spatial dataset that monitors mangrove deforestation globally at high spatio‐temporal resolutions. These data can be used to drive the mangrove research agenda, particularly as it pertains to monitoring of mangrove carbon stocks and the establishment of baseline local mangrove forest inventories required for payment for ecosystem service initiatives.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Impact of Eating Probiotic Yogurt on Colonization by Candida Species of the Oral and Vaginal Mucosa in HIV-Infected and HIV-Uninfected Women - Haihong Hu; Daniel J. Merenstein; Cuiwei Wang; Pilar R. Hamilton; Mandy L. Blackmon; Hui Chen; Richard A. Calderone; Dongmei Li (Mycopathologia, 2013)

Fine mapping of type 1 diabetes regions Idd9.1 and Idd9.2 reveals genetic complexity - Emma E. Hamilton-Williams; Daniel B. Rainbow; Jocelyn Cheung; Mikkel Christensen; Paul A. Lyons; Laurence B. Peterson; Charles A. Steward; Linda A. Sherman; Linda S. Wicker (Mammalian Genome, 2013)

Invasion facilitates hybridization with introgression in the Rattus rattus species complex - JUSTIN B. LACK; DANIEL U. GREENE; CHRIS JOHN CONROY; MEREDITH J. HAMILTON; JANET K. BRAUN; MICHAEL A. MARES; RONALD A. VAN DEN BUSSCHE (Molecular Ecology, 2012)
Biological invasions result in novel species interactions, which can have significant evolutionary impacts on both native and invading taxa. One evolutionary concern with invasions is hybridization among lineages that were previously isolated, but make secondary contact in their invaded range(s). Black rats, consisting of several morphologically very similar but genetically distinct taxa that collectively have invaded six continents, are arguably the most successful mammalian invaders on the planet. We used mitochondrial cytochrome b sequences, two nuclear gene sequences (Atp5a1 and DHFR) and nine microsatellite loci to examine the distribution of three invasive black rat lineages ( Rattus tanezumi , Rattus rattus I and R. rattus IV) in the United States and Asia and to determine the extent of hybridization among these taxa. Our analyses revealed two mitochondrial lineages that have spread to multiple continents, including a previously undiscovered population of R. tanezumi in the south‐eastern United States, whereas the third lineage ( R. rattus IV) appears to be confined to Southeast Asia. Analyses of nuclear DNA (both sequences and microsatellites) suggested significant hybridization is occurring among R. tanezumi and R. rattus I in the United States and also suggest hybridization between R. tanezumi and R. rattus IV in Asia, although further sampling of the latter species pair in Asia is required. Furthermore, microsatellite analyses suggest unidirectional introgression from both R. rattus I and R. rattus IV into R. tanezumi . Within the United States, introgression appears to be occurring to such a pronounced extent that we were unable to detect any nuclear genetic signal for R. tanezumi , and a similar pattern was detected in Asia.

Validating motor unit firing patterns extracted by EMG signal decomposition - Hossein Parsaei; Faezeh Jahanmiri Nezhad; Daniel W. Stashuk; Andrew Hamilton-Wright (Medical & Biological Engineering & Computing, 2011)

Conserved regulatory motifs at phenylethanolamine N-methyltransferase (PNMT) are disrupted by common functional genetic variation: an integrated computational/experimental approach - Juan L. Rodríguez-Flores; Kuixing Zhang; Sun Woo Kang; Gen Wen; Sajalendu Ghosh; Ryan S. Friese; Sushil K. Mahata; Shankar Subramaniam; Bruce A. Hamilton; Daniel T. O’Connor (Mammalian Genome, 2010)

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

A standardized nomenclature for the mouse and rat prolactin superfamilies - Michael J. Soares; S. M. Khorshed Alam; Mary Lynn Duckworth; Nelson D. Horseman; Toshihiro Konno; Daniel I. H. Linzer; Lois J. Maltais; Marit Nilsen-Hamilton; Kunio Shiota; Jennifer R. Smith; Michael Wallis (Mammalian Genome, 2007)

Resource‐based adaptive divergence in the freshwater fish Telmatherina from Lake Matano, Indonesia - DENIS ROY; GORD PATERSON; PAUL B. HAMILTON; DANIEL D. HEATH; G. DOUGLAS HAFFNER (Molecular Ecology, 2007)
Adaptive radiations are an important source of biodiversity, but resolving which ecological pressures seed these processes in natural systems remains difficult. Here the adaptive radiation among Telmatherina , a genus of freshwater fish endemic to an ancient lake in central Sulawesi, Indonesia, was examined to determine its causal root. We demonstrate that all Telmatherina in this lake can be categorized into three lineages each possessing specialized skull shapes and pharyngeal jaw bones allowing them to exploit different resources. These data demonstrate a natural example of how resource partitioning has likely initiated adaptive radiation in a resource limited environment.

The scaling of motor noise with muscle strength and motor unit number in humans - Antonia F. de C. Hamilton; Kelvin E. Jones; Daniel M. Wolpert (Experimental Brain Research, 2004)

The nitrogen budget of a pine forest under free air CO2 enrichment - Adrien C. Finzi; Evan H. DeLucia; Jason G. Hamilton; Daniel D. Richter; William H. Schlesinger (Oecologia, 2002)